Fertility Preservation Is Safe for Serous Borderline Ovarian Tumors. Issue 8 (October 2016) - Vancraeynest, Eveline; Moerman, Philippe; Leunen, Karin; Amant, Frédéric; Neven, Patrick; Vergote, Ignace
Abstract : Objectives: This study aimed to determine the overall survival (OS) and progression-free interval and the influence of fertility-preserving surgery (FPS) versus radical surgery (RS) in patients with serous borderline ovarian tumor (BOT). Methods: Clinical parameters of patients with serous BOT treated between 1993 and 2013 in one institution were retrospectively investigated. All tumors were examined by one pathologist with experience in gynecological pathology. Results: One hundred thirty-two patients with serous BOT (inclusive 16 microinvasive) were analyzed (45% were ⩽40 years), with a median follow-up of 6 years. Thirty-two percent (42/132) of the patients received FPS; 14% (18/132) relapsed (invasive or borderline). The 5-year progression-free survival was 89%. The risk of recurrence was higher in patients 40 years or younger ( P = 0.019), after FPS ( P = 0.002), in patients with a higher International Federation of Gynecology and Obstetrics (FIGO) stage ( P = 0.016), for bilateral BOT ( P = 0.0132), and for the micropapillary variant ( P = 0.067). The OS at 5 years was 97%. There was no statistically significant difference in OS between FPS and RS [all (6 of 90) patients, except for 1, with RS died]. One patient died of relapsed BOT. Among the recurrences, low-grade invasive carcinoma was diagnosed in 4 patients. Three of these 4 patients were originally operated radically, 2 had a micropapillary variant FIGO stage III, and 1 had a papillary pattern FIGO stage II with microinvasion; all 3 had noninvasive implants and are alive. One patient with a micropapillary variant, FIGO stage IIIC with microinvasion and invasive implants, received FPS and died of disease. Conclusions: The risk of recurrence is higher after FPS compared with RS; however, no influence on OS was observed. This was because most of the patients relapsed as BOT. Fertility preservation is justified in young patients with serous borderline tumors.